Assessing the Credibility of Child Alibi Corroborators. Issue 2 (15th March 2021) - Snow, Mark D.; Eastwood, Joseph
ABSTRACT: Across two studies, we investigated the effect of alibi corroborator age on alibi assessment. In Study 1, we examined the impact of the alibi corroborator's age (i.e., 8- vs. 25-year-old) and relationship with the suspect (i.e., stranger vs. neighbor vs. son) on five dependent measures related to corroborator credibility and suspect guilt. In Study 2, we examined the impact of the corroborator's age (i.e., 4- vs. 8- vs. 25-year-old) and the perceived level of cognition needed to remember the alibi event (i.e., delayed vs. recent event). Participants' perceptions were somewhat more favorable toward the 8-year-old corroborator, compared to a 4- or 25-year-old. The current results help to shed light on an existing inconsistency in the alibi literature regarding the impact of corroborator age on alibi assessment outcomes.